Association between immune checkpoint inhibitors and vascular endothelial growth factor targeted therapy with cardiovascular events. (3rd October 2022) - Drobni, Z; Gong, J; Raghu, V; Zafar, A; Gongora, C; Quinaglia, T; Suero-Abreu, G; Gilman, H; Gao, X; Sullivan, R; Merkely, B; Reynolds, K; et al.
Abstract: Background: The use of immune checkpoint inhibitors (ICI) has been associated with a 3-fold higher risk for cardiovascular events as compared to cancer patients who did not receive ICI. Therapies targeting vascular endothelial growth factor (VEGF) have also been associated with a wide range of cardiovascular events. The combination use of ICIs and VEGF inhibitors is currently approved as a treatment for patients with renal-cell carcinoma, hepatocellular carcinoma, non-small cell lung cancer, and endometrial cancer. Data are lacking whether the combination of ICIs and VEGF-targeted therapy is associated with an additional increase in cardiovascular events. Purpose: To evaluate whether the combination use of ICI and VEGF targeted therapies are associated with a higher risk of cardiovascular events as compared to ICI therapy alone, we performed a retrospective matched case-control study. Methods: Cases received both ICI and VEGF-targeted therapy (n=157), and control patients (n=157) only received ICI therapy. The primary outcome was a composite of cardiovascular events (myocardial infarction, coronary revascularization, ischemic stroke, deep venous thrombosis, and pulmonary embolism). Patients were censored at time of first event or at last date of follow up. Cox proportional hazard regression analysis was performed to calculate hazard ratio (HR) with 95% confidence interval (CI), counting only the first cardiovascular event. Results: Baseline characteristics for the cases and controls are shown in Table 1. Overall cases (combination ICI and VEGF inhibitor) and controls (ICI alone) were not different with respect to age, type of cancer, and a prior history of any cardiovascular event. Cases received more ICI cycles as compared to controls (median of 7 [4–17] cycles vs. 4 [2–10] cycles, P<0.001). Cases also had a longer follow-up time (334 [127–663] days vs. 201 [60–564] days, P=0.008) as compared to the control group. As compared to ICI alone, a similar risk for a composite cardiovascular event was observed in those who received both ICI and VEGF-targeted therapy (HR, 0.70 [95% CI, 0.39–1.25]; P=0.23, Table 1). In total, 21/157 patients had a composite cardiovascular event among the cases, who received the combination of ICI and VEGF inhibitor (9 DVT, one MI, 9 PE, two ischemic strokes) as compared to 25/157 among the controls, who received ICI alone (14 DVT, 3 MI, 7 PE, one ischemic stroke). The median time to event was not different between the two groups (126 [98–260] days vs. 145 [28–205] days, P=0.47). Conclusion: We found that among 157 patients who received a combination of ICI and VEGF-targeted therapy and 157 matched control patients who only received ICI therapy, the risk for cardiovascular events was not different between the two groups. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding.